Integrated Islamic Time Management Model for Tahfidz Students based on Surah Al-'Ashr as a Productivity Framework - Norman, Efrita; Rahmawati, Firda Dwi; Paramansyah, Arman; Alawiyah, Tuti (Universitas Nurul Jadid, 2024)
This study aims to develop an effective time management model for Tahfidz students in Islamic boarding schools by integrating Islamic principles and modern productivity strategies. Good time management is essential for students who must balance memorizing the Qur’an and academic tasks. However, many students have difficulty managing their busy schedules, which causes stress and decreased productivity. This study uses a qualitative case study approach with data collection techniques in the form of in-depth interviews, participant observation, and document analysis in a Tahfidz Islamic boarding school in Indonesia. The main findings of this study indicate that students define time management as a way to organize and utilize time productively. They apply strategies such as determining priorities, making to-do lists, and allocating time according to activity portions. However, the main challenge faced is difficulty managing academic tasks amidst a tight memorization schedule. This study proposes an Al-'Ashr-Based Time Management Model that emphasizes four main principles: awareness of the importance of time, utilization of time for good deeds, reminding each other of the truth, and resilience in facing tests. The contribution of this study is to provide a model that combines spiritual motivation with a structured scheduling method. The implication of this study is the importance of implementing a more flexible scheduling system to improve efficiency and balance between memorization and academic tasks in Islamic boarding schools.